2010
DOI: 10.2527/jas.2009-2170
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic maturity at birth and neonate lamb survival: Association among maternal factors, litter size, lamb birth weight, and plasma metabolic and endocrine factors on survival and behavior1

Abstract: This paper reports an investigation into metabolic and endocrine maturity in the neonate lamb and the relationships between litter size, birth weight, and maternal metabolic and endocrine variables on behavior at birth and survival over the first 72 h of life. Data were from multiparous, fine-wool Merino ewes (n = 150; equal numbers of single-lamb and twin-lamb bearing status) lambed on pasture after late gestational glucocorticoid treatments. Stepwise multiple regression analysis was used to investigate relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…Furthermore, the birthweights of the lambs were close to the range of 4.5-5.5 kg, at which maximum survival occurs, and the rectal temperatures and blood glucose concentrations at birth were similar to those reported previously, therefore indicating that the lambs were not at an increased risk of death in the first 72 h of life (Stafford et al 2007;Miller et al 2010;Chniter et al 2013). On average, only 4.6% of lambs born alive died within the first 72 h of life in the present study, which is considerably lower than the expected mortality of 20-30% (Oldham et al 2011;Hawken et al 2012;Hinch and Brien 2014).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, the birthweights of the lambs were close to the range of 4.5-5.5 kg, at which maximum survival occurs, and the rectal temperatures and blood glucose concentrations at birth were similar to those reported previously, therefore indicating that the lambs were not at an increased risk of death in the first 72 h of life (Stafford et al 2007;Miller et al 2010;Chniter et al 2013). On average, only 4.6% of lambs born alive died within the first 72 h of life in the present study, which is considerably lower than the expected mortality of 20-30% (Oldham et al 2011;Hawken et al 2012;Hinch and Brien 2014).…”
Section: Discussionsupporting
confidence: 62%
“…On average, 30% of all lambs born will die before weaning, and ~80% of lamb deaths occur in the first 48-72 h of life (Miller et al 2010;Oldham et al 2011;Hawken et al 2012;Hinch and Brien 2014;Paganoni et al 2014). Lamb birthweight is the greatest contributor to lamb survival and is strongly influenced by ewe nutrition during pregnancy (Oldham et al 2011;Paganoni et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that in flocks managed permanently outdoors, harsher conditions in terms of low temperatures, wind and precipitation decrease early neonatal lamb survival [ 10 , 29 , 31 ]. With very few exceptions, lambing takes place indoors in flocks in Norway, which should be expected to prevent neonatal deaths caused by adverse weather conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Improved lamb viability beyond 72 h is associated with decreased vulnerability to chilling, singleton status, higher pre-suckling body temperature, decreased pre-suckling glucose concentrations, high plasma concentration of proteins, lipids and immunoglobulins, and a moderate rise in neonatal cortisol concentration (Eales et al, 1982;Miller et al, 2010). Being bigger is an advantage in terms of vigour and thermoregulation, as lambs are more efficient in their suckling activity and in resisting cold exposure.…”
Section: Biological Factors Involved In Lamb and Kid Mortality/survivalmentioning
confidence: 99%